PENGGUNAAN FITUR LIVE STREAMING SEBAGAI MARKETING COMMUNICATION DAN LEADCUSTOMER TERHADAP PENINGKATAN PENJUALAN - Ana Ramadhayanti (MANAJEMEN DEWANTARA, 2023)
The development of the digital world continues to increase, so that it has a very helpful impact, especially for a seller or buyer. One of the most visible things is the end of shopping for various online shopping sites that offer mutual benefits and conveniences, as currently trending is the live streaming feature. This feature is certainly very helpful between buyers and sellers in marketing a product. In addition to the live streaming feature strategy carried out by a seller, another strategy carried out by the seller is to have a customer pool (lead customer). They have gathered prospective buyers long before the product was released. before the product is released. All of these things are basically in order to be able to increase sales, although to show this, of course, further research must be carried out. The research carried out in this case was using a quantitative research method with a data pooling method in the form of distributing buyer questionnaires on the website with a sample of residents of the Tanjung Priok Lagoa Horizon II sub-district. The questionnaire that has been obtained will be processed using SPSS software. The calculation results show that there is a strong and positive influence between the Live Streaming feature and Leadcustomers on increasing sales. With the results of this observation, it is hoped that it will have a use value for the community, both for sellers and buyers.